3D spheroids of human placenta-derived mesenchymal stem cells attenuate spinal cord injury in mice - Junhao Deng (Nature Publishing Group, 2021)
Abstract Mesenchymal stem cell (MSC) is an absorbing candidate for cell therapy in treating spinal cord injury (SCI) due to its great potential for multiple cell differentiation, mighty paracrine secretion as well as vigorous immunomodulatory effect, of which are beneficial to the improvement of functional recovery post SCI. However, the therapeutic effects of MSC on SCI have been limited because of the gradual loss of MSC stemness in the process of expanding culture. Therefore, in this study, we aimed to maintain those beneficial properties of MSC via three-dimensional spheroid cell culture and then compared them with conventionally-cultured MSCs in the treatment of SCI both in vitro and in vivo with the aid of two-photon microscope. We found that 3D human placenta-derived MSCs (3D-HPMSCs) demonstrated a significant increase in secretion of anti-inflammatory factors and trophic factors like VEGF, PDGF, FGF via QPCR and Bio-Plex assays, and showed great potentials on angiogenesis and neurite morphogenesis when co-cultured with HUVECs or DRGs in vitro. After transplantation into the injured spinal cord, 3D-HPMSCs managed to survive for the entire experiment and retained their advantageous properties in secretion, and exhibited remarkable effects on neuroprotection by minimizing the lesion cavity, inhibiting the inflammation and astrogliosis, and promoting angiogenesis. Further investigation of axonal dieback via two-photon microscope indicated that 3D-HPMSCs could effectively alleviate axonal dieback post injury. Further, mice only treated with 3D-HPMSCs obtained substantial improvement of functional recovery on electrophysiology, BMS score, and Catwalk analysis. RNA sequencing suggested that the 3D-HPMSCs structure organization-related gene was significantly changed, which was likely to potentiate the angiogenesis and inflammation regulation after SCI. These results suggest that 3D-HPMSCs may hold great potential for the treatment of SCI.